Assessing the costs of alternative development paths in Australian cities. - Newman, Peter; Trubka, R.; Bilsborough, D. (2009)
This paper explores the economic impacts associated with two iconic development types (urban redevelopment and fringe development) as their embodied costs are broken down into the categories of infrastructure provision, transportation costs, greenhouse gas emissions and health costs. The findings show that there are substantial cost savings associated with urban redevelopment. By far, the largest figures are associated with infrastructure and transportation while GHG emissions and health constitute smaller portions of total costs, although the latter do have serious implications in terms of the attainability of national emissions reductions targets (redevelopment will save 4,400 tonne of GHG per year for 1,000 dwellings) and the Australian population’s health and well being (now one of the most obese populations in the world). Emissions and health savings are closely related to active forms of travel that are only realizable in areas with high levels of amenity and servicing and high levels of transit access. Their cost savings over a 50 year urban lifetime are quite modest, $19.32 million and $4.23 million for 1000 dwellings, but if these more walkable, low emission developments are pursued then the savings in transport and infrastructure for 1000 dwellings are in the order of $86 million up-front for infrastructure and $250 million for annualized transportation costs over 50 years. A simple model is developed from these assessments that can be used to predict urban development costs associated with any proposed development in Australian cities or with the associated urban development from any major infrastructure decisions.